Gasoline Rationing in the United States, I - Maxwell, James A.; Balcom, Margaret N. (Quarterly Journal of Economics, 1946)
The introduction of rationing: the Eastern gasoline shortage, 561; nation-wide rationing, 564. — The separation of District I, 567. — The “pleasure driving” ban, 569. — Other steps to reduce consumption, 570. — The non-recoverable “B” and “C” cut, 572. — End of the “pleasure driving” ban, 572. — Jurisdictional dispute between OPA and PAW, 573. — Spread of the gasoline shortage: relaxation of the program, 576; the shortage spreads to Districts II and III, 577; the shortage spreads to Districts IV and V, 579; the program settles down, 580. — The local board system, 581.